The odyssey of homework during the COVID-19 pandemic - Eugen Bruno Ștefan (Amfiteatru Economic Journal, 2021)
Working from home has brought a number of changes in the lives, habits and ways of working of many employees. The article analyzes some of these changes starting from a survey conducted at the end of 2020 on a national sample of 554 subjects. The results were grouped on several major topics: resources, changes, advantages/disadvantages, which resulted in three analysis models: CALIPSO, CIRCE and CICLOP. These are the names of famous characters from Homer's Odyssey, and the comparison with them shows that the way back from office work to home work was not without its adventures and consequences. The COVID-19 pandemic produced changes in the attitudes and behaviors of those who experienced work from home in the second half of 2020. The correlations show significant differences between types of employees, such as those between public servants and those in the private sector. or between those with doctoral studies and those with fewer years of schooling.
Keywords: A14; D23; D91; E24; M54; 330; telework; pandemic; Odyssey